DsbA-L prevents obesity-induced inflammation and insulin resistance by suppressing the mtDNA release-activated cGAS-cGAMP-STING pathway - Bai, Juli; Cervantes, Christopher; Liu, Juan; He, Sijia; Zhou, Haiyan; Zhang, Bilin; Cai, Huan; Yin, Dongqing; Hu, Derong; Li, Zhi; Chen, Hongzhi; Gao, Xiaoli; et al. (Proceedings of the National Academy of Sciences - PNAS, 2017)
Chronic inflammation in adipose tissue plays a key role in obesity-induced insulin resistance. However, the mechanisms underlying obesity-induced inflammation remain elusive. Here we show that obesity promotes mtDNA release into the cytosol, where it triggers inflammatory responses by activating the DNA-sensing cGAS-cGAMP-STING pathway. Fat-specific knockout of disulfide-bond A oxidoreductase-like protein (DsbA-L), a chaperone-like protein originally identified in the mitochondrial matrix, impaired mitochondrial function and promoted mtDNA release, leading to activation of the cGAS-cGAMP-STING pathway and inflammatory responses. Conversely, fat-specific overexpression of DsbA-L protected mice against high-fat diet-induced activation of the cGAS-cGAMP-STING pathway and inflammation. Taken together, we identify DsbA-L as a key molecule that maintains mitochondrial integrity. DsbA-L deficiency promotes inflammation and insulin resistance by activating the cGAS-cGAMP-STING pathway. Our study also reveals that, in addition to its well-characterized roles in innate immune surveillance, the cGAS-cGAMP-STING pathway plays an important role in mediating obesity-induced metabolic dysfunction.